(untitled) (Ameghiniana, 2013)
Reasons of space compeled the author to remove from the original text the part destined to the geological matters, which will be published separately. He proposes in it the denomination of "Kawas sea" for the Upper Cretaceous and Lower Tertiary Atlantic sea deeply setted in the Patagonian continent, and those of "Maastrichtian transgression" -considering the moment of its entrance- or "Schiller’s transgression" for the dynamic phenomenon involved. The present paper is restricted to some notices on the ecology of the littoralline of that sea in its neo-Maastrichtian (until meso-Maastrichtian, sensu Bertels 1969) moment. The concept of "littoral" is here a large one, so including the coast, the sea-shore and the beach. In an ideal cross section, from sea to continent, the author presents the following actors in that stage: Hadrosaurian dinosaurs (Ornithischian) -occasionally adventurers in open sea-; crocodiles; tortoises; mud-birds -which shared the lagoons by the sea with fishes of mixed habits, lunged fishes, small Coelurosaurian dinosaurs (Saurischian) and other vertebrates (and invertebrates as well)-. To the interior of the stage, the same Hadrosaurians and some small Titanosaurs (Saurischian) shared fresh water lagoons with fishes, tortoises ... Finally , in the open continent, larger lagoons lodged the big Titanosaurs (f.i. Laplatasaurus),crocodiles, tortoises and fishes... spyed from solid ground by Carnosaurian dinosaurs, mud-birds, etc. Going to the floristic and climatic respects, the author -through the comparison with similar associations of identical age in North America, in the Lance and Hell Creek Formations- concludes: first, similar climatic conditions, compared by Estes with those of the " ... Gulf and South Atlantic coastal plains of the United States today ... " (Estes 1964); second, a continuity -of some sort- along the paleo-Atlantic sea-shore between South America and North America during the Maastrichtian times.